Enhancing Arabic Language Acquisition: Effective Strategies for Addressing Non-Native Learners' Challenges - Sultan Almelhes (MDPI AG, 2024)
The Arabic language has gained significant global recognition, with a growing number of non-Arab individuals learning it as a second language. Despite this trend, learners of Arabic face various challenges that have not been thoroughly examined. This study aimed to investigate the challenges encountered by learners of the Arabic language and to determine the factors that contribute to effective language learning and use. Data from 444 non-native speakers learning Arabic as a second language were analyzed with SPSS 27 using a descriptive approach. The results indicated that Arabic instructors should focus on improving feedback practices, developing customized curricula, and incorporating technology and multimedia resources into their teaching methods. Furthermore, this study highlights the importance of integrating cultural components and accommodating diverse learners in the classroom. To improve speaking proficiency, learners can engage in activities such as listening to radio broadcasts, collaborating with classmates, and building relationships with Arabic-speaking friends. The results of this research provide insights that can assist instructors of Arabic as a second language in supporting learners, improving their abilities to learn and communicate in Arabic.